2020
DOI: 10.3390/antiox9050424
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Walnut (Juglans regia L.) Kernel and Walnut Septum Extract in a D-Galactose-Induced Aging Model and in Naturally Aged Rats

Abstract: Antioxidant dietary intervention is considered a potential strategy in delaying age-related dysfunctions. In this study of 56 days, we assessed the antioxidant effects of walnut kernel (WK) and walnut septum extract (WSE) in a D-galactose (D-gal)-induced aging model and in a naturally aged rat model. Young Wistar rats, treated with D-gal (1200 mg/week), and old rats received daily WK or WSE added to the feed. After 8 weeks, blood, liver, and brain samples were collected and hematological, biochemical, oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 56 publications
4
29
0
Order By: Relevance
“…As in other studies [ 35 ], a more plausible explanation would be that reduced ROS concentration is related to the modulation of endogenous antioxidant defense systems. The in vivo antioxidant capacity of WSE was also reported in a D-gal-induced aging model in rats where administration of this extract for 8 weeks statistically decreased the ROS levels in brain and liver tissues [ 36 ]. The results obtained indicate that WSE possess in vitro and in vivo antioxidant potential, thus being in accordance with previously published other studies on walnut-derived extracts [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other studies [ 35 ], a more plausible explanation would be that reduced ROS concentration is related to the modulation of endogenous antioxidant defense systems. The in vivo antioxidant capacity of WSE was also reported in a D-gal-induced aging model in rats where administration of this extract for 8 weeks statistically decreased the ROS levels in brain and liver tissues [ 36 ]. The results obtained indicate that WSE possess in vitro and in vivo antioxidant potential, thus being in accordance with previously published other studies on walnut-derived extracts [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that changes in NO were mostly reported in asthmatic patients that present eosinophilic inflammation, while no correlation between exhaled NO and other respiratory pathologies characterized by cough were demonstrated [ 49 ]. In a previous study in which we evaluated the anti-aging potential of WSE, no changes in this parameter were observed in liver and brain tissues of naturally aged animals [ 36 ]. Alternatively, these results could be due to the fact that whole lung tissues were used for the assay, and local changes of NO concentration in superficial tissue could have been masked by the bulk of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the dose-dependent antiproliferative effect of walnut septum extract on human A549 lung adenocar-cinoma, human T47D-KBluc and MCF-7 breast cancer cell lines has been demonstrated ( 70 ). In addition, walnut consumption or walnut extracts showed antioxidant, anti-inflammatory and anti-aging properties in the brain ( 26 , 29 , 32 ). However, the antitumor activity of walnut septum extract against one of the most aggressive brain tumors, glioblastoma, has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in both animal and human studies it was demonstrated that a walnut diet reduces the brain-accumulation of damaged proteins and reduces brain inflammation associated with aging (26)(27)(28). A previous study has highlighted the strong antioxidant effects of walnut septum extracts (29), suggesting a possible role of such extracts in the maintenance of brain homeostasis (30,31). Therefore, these studies have demonstrated that walnut consumption or walnut extracts are protective for brain aging (32), paving the way for further studies investigating brain tumors.…”
Section: The Double Effect Of Walnut Septum Extract (Juglans Regia Lmentioning
confidence: 99%
“…In brief, plasma nitrate was reduced to nitrite, using vanadium chloride, under acidic conditions, at 37 • C, in a 96 well microtiter plate. The newly obtained nitrite, together with pre-existent plasma nitrite were determined spectrophotometrically, using the Griess reaction (diazotization of sulfanilic acid, followed by coupling with alpha-naphthylamine) [40].…”
Section: Circulating Antioxidants Levelsmentioning
confidence: 99%